Upaya Pelestarian Musik Tradisional Canang Limo dan Canang Anam di Nagari Abai Kabupaten Solok Selatan - Wansah, Faisal; Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
Program The purpose of this research is to find out how the Abai community efforts in preserving the traditional music of canang limo and canang anam in Abai nagari, South Solok Regency. This type of research is qualitative research with a descriptive method of analysis. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study uses primary data and secondary data. Data collection techniques are carried out by means of observation, interviews, and documentation. The steps of analyzing data are data collection, describing data and concluding data. The results of the study show that efforts to preserve Canang Limo and Canang Anam have been carried out well by a female artist named Mak Maraya who has participated in various traditional events in Nagari. The art of Cnang Limo and Canang Anam, a traditional art of the community that has been passed down from generation to generation from the ancestors of.